Model of Flow Resistance Coefficient for a Fragment of a Porous Material Deposit with Skeletal Structure - Grzegorz Wałowski (Energies, 2021)
The hydrodynamic conditions resulting from the permeability of porous materials are based not only on the assessment of the gas flow through these materials, but also the losses related to the pressure energy in this flow. Flow resistance is a direct measure of this loss. The aim of this experimental research was to evaluate the flow resistance of the porous material in relation to the gas flow. The research was carried out on a material with a slit-porous structure. The tests were carried out on a system for measuring gas permeability under the conditions of gas bubbling through the char. The issue of the total pressure drop process in the porous bed was considered in the Reynolds number category. The coefficient of flow resistance for the char was determined and the value of this coefficient was compared with the gas stream, and an experimental evaluation of the total pressure drop on the porous bed was made. The novelty of this article is the determination of the tortuosity and the gas permeability coefficient for a solid of any shape—a rigid skeleton.